Sistem Pakar dengan Metode Certainty Factor dalam Analisis Penyakit Herpes Zoster pada Manusia - Teguh Junaidi; Yuhandri Yunus (SEULANGA SYSTEM PUBLISHER, 2021)
Herpes Zoster or shingles is an infection caused by the varicella zoster virus. Herpes Zoster is also called shingles because there will be blisters on the skin in the form of lines or small areas on one side of the face or body and it feels quite hot like burning. Usually the patient experiences complaints in the form of reddish spots and air-filled bubbles appear. Designing an expert system in order to help users with the early symptoms of Herpes Zoster, as well as indicators of the type of Herpes Zoster disease which they suffer through the results of direct consultation through the system. The data used in this study were obtained from direct interviews with experts, namely Dr. Qaira Anum Sp.KK at the RSI hospital. Ibnu Sina Padang as a specialist in skin and venereal diseases. The data obtained were data on the types of Herpes Zoster, the symptoms of each type of Herpes Zoster, the weight of each type of existing symptoms, and the solution or prevention of each type of Herpes Zoster disease. This research was assisted by using the Certainty Factor method in order to facilitate the process of determining what type of Herpes Zoster disease suffered by users who consult through the system based on the symptoms felt by each user. The result of testing this method is that there are 100% of 10 testing data. Based on the accuracy of the findings for this system, this study is very precise in the level of identity known to Herpes Zoster in humans. Expert system of examiners can specifically identify Herpes Zoster. Through this Certainty Factor method, the level of accuracy is accurate and can help veterinarians improve their accuracy to identify Herpes Zoster in humans.